The Role of Parents' Attention in the Moral Development of Children in the Amid of COVID-19 Pandemic - Susanto, Eri; Suyadi, Suyadi (Universitas Pendidikan Ganesha, 2020)
The current covid-19 pandemic has caused the child's needs to be less fulfilled for the attention and guidance of parents, which will undoubtedly affect the aspects of children's moral development. This research was conducted to identify the role of parental attention in the moral development of elementary school children during the Covid-19 pandemic. This research uses qualitative methods with literature studies from several sources, both print and electronic media, as well as books and online journals. The research technique used is the documentation technique in the form of notes, books, papers or articles, journals, and news. Validity test, researchers used the triangulation of data sources. The literature review analysis uses the content analysis paradigma presentation of data using informal presentation methods. The results of this study are based on a survey from the Ministry of Education and Culture, namely that around 90% of parents accompany their children during SFH, and only 3,4% of children do not receive assistance from their parents because their parents work outside the home. This research concludes that it is essential for parents to pay attention to the moral development of their children, especially during the Covid-19 pandemic, in general, parents have played a role in accompanying their children during the Covid-19 and SFH pandemic.